Maternal mortality in a tertiary hospital of North India- analysis of causes and risk factors - Miglani, Urvashi; Kohli, Jasmine K.; Laul, Poonam; Grover, Monika S.; Madan, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Approximately 529,000 women die from pregnancy-related causes annually and almost 99% of these occur in developing nations. Even with decline, India still is one of the major contributors to maternal deaths in the world. Hence, the present study was conducted to assess the causes, sociodemographic factors and level of delay influencing maternal mortality. Methods: A retrospective descriptive study based on all maternal deaths within 2.5 years from June 2020 to December 2022 in tertiary care center New Delhi was included. All deaths were assessed for sociodemographic risk factor and processed using descriptive statistics for various variables. Results: During the study 77 deaths were identified. 48 deaths were direct and 29 were indirect maternal deaths. Sepsis and infectious diseases were the leading cause of direct and indirect maternal death respectively. 47% women died at more than 34 weeks’ gestation.12 women died undelivered. 65 women who died in the postpartum period, caesarean section was performed in 32%. Of total deaths 53 women were unbooked and level 1 delay in 78% cases. Conclusions: Education and awareness of importance of antenatal care, diagnosis and management of anemia to be given prime importance. Institutional deliveries to be encouraged. Optimization of comorbid conditions in the preoperative period is quintessential.